Differences in Disrupted Dynamic Functional Network Connectivity Among Children, Adolescents, and Adults With Attention Deficit/Hyperactivity Disorder: A Resting-State fMRI Study - Agoalikum, Elijah; Klugah-Brown, Benjamin; Yang, Hang; Wang, Pan; Varshney, Shruti; Niu, Bochao; Biswal, Bharat (Frontiers in Human Neuroscience, 2021)
Attention deficit hyperactivity disorder (ADHD) is one of the most widespread mental disorders and often persists from childhood to adulthood, and its symptoms vary with age. In this study, we aim to determine the dynamic functional network connectivity differences in adult, adolescent, and child ADHD using resting-state functional magnetic resonance imaging (rs-fMRI) data consisting of 35 children (8.64 ± 0.81 years), 40 adolescents (14.11 ± 1.83 years), and 39 adults (31.59 ± 10.13 years). We hypothesized that functional connectivity is time-varying and that there are within- and between-network connectivity differences among the three age groups. Nine functional networks were identified using group ICA, and four FC-states were recognized based on their dynamic functional network connectivity (dFNC) pattern. Fraction of time, mean dwell time, transition probability, degree-in, and degree-out were calculated to measure the state dynamics. Out of the nine networks, seven networks showed significant dFNC differences between the three groups. The DMN, VN, and SMN were frequently found to show network connectivity differences between the three groups. State 4 was found to show significant differences between the three groups in all the measures. Our findings imply abnormal dynamic interactions and dysconnectivity associated with ADHD, and these abnormalities differ between the three ADHD age groups. Given the dFNC differences between the three groups in the current study, our work further provides new insights into the pathophysiology of ADHD, which can serve as a guide in the clinical diagnosis of ADHD.